Studies on Sudan Desert sheep: 1. Effect of feeding to lambs of poor quality dry desert grass (humra) and subsequent refeeding on a high plane of nutrition on live weight growth, carcass yield and offals - Gaili, E.S.E.; Mahgoub, O. (1982)
Forty–two weaned Sudan Desert lambs of both sexes were divided into three equal sex and age groups and were randomly assigned to one of three diets: Humra + limited amount of cottonseed cake and a complete ration (dura 44 % cottonseed cake 25% dry humra 29% salt 1.5% and vitamin minerals 0.5%). All diets were fed adlibitum for eleven weeks. Then differential feeding was stopped and each group was fed ad libitum on the complete ration for twelve weeks. Two lambs from both sexes were chosen at random for each nutritional treatment, and were slaughtered before the beginning of the trial. Half of the remaining lambs in each treatment was slaughtered at the end of the differential feeding period and the other half at the end of the trial. Generally, the live weight gain of lambs fed on Humra, with or without cottonseed cake, was poor whereas lambs fed on the complete ration made significantly (p